2021
DOI: 10.1155/2021/5570796
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Improves Epithelial Barrier Integrity of Caco-2 Monolayers by Inhibiting Endoplasmic Reticulum Stress and Subsequent Apoptosis

Abstract: Curcumin is a natural polyphenol and is supposed to possess antioxidant, anti-inflammatory, anticancer, and antiapoptotic properties. Although some studies have reported the therapeutic effects of curcumin on ulcerative colitis (UC), the specific mechanism remains unclear. An in vitro coculture model of Caco-2 and differentiated THP-1 cells was established. After administration of curcumin (10 μM), Western blot analysis was performed to evaluate the protein levels of tight junction (TJ) proteins zonula occlude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“… 116 Zhou et al have shown that curcumin improves intestinal barrier integrity by controlling endoplasmic reticulum stress and subsequent apoptosis. 117 Tian et al have found that curcumin maintains the intestinal permeability and restores epithelial structure by enhancing ZO-1 protein expression through tumor necrosis factor (TNF)-α-related pathway in rats with intestinal ischemia-reperfusion injury. 118 Cao et al have unveiled that curcumin enhanced intestinal barrier and mitochondrial function by Parkin-dependent mitophagy through AMPK activation and subsequent nuclear translocation of transcription factor EB in vitro and in pigs with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“… 116 Zhou et al have shown that curcumin improves intestinal barrier integrity by controlling endoplasmic reticulum stress and subsequent apoptosis. 117 Tian et al have found that curcumin maintains the intestinal permeability and restores epithelial structure by enhancing ZO-1 protein expression through tumor necrosis factor (TNF)-α-related pathway in rats with intestinal ischemia-reperfusion injury. 118 Cao et al have unveiled that curcumin enhanced intestinal barrier and mitochondrial function by Parkin-dependent mitophagy through AMPK activation and subsequent nuclear translocation of transcription factor EB in vitro and in pigs with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we identified the exact molecular mechanisms via which LA alleviated UC by regulating ferroptosis in vitro . Previous research has shown that ER stress mediated colonic epithelial cell apoptosis during UC and that ferroptosis also can be induced by ER stress 38,39 . Using the erastin‐induced ferroptosis cell model, we found that pretreatment with LA notably rescued Caco‐2 cells from ferroptosis challenged by erastin.…”
Section: Discussionmentioning
confidence: 60%
“…Previous research has shown that ER stress mediated colonic epithelial cell apoptosis during UC and that ferroptosis also can be induced by ER stress. 38,39 Using the erastin-induced ferroptosis cell model, we found that pretreatment with LA notably rescued Caco-2 cells from ferroptosis challenged by erastin. Interestingly, our current results showed that GPR78, CHOP, p-eIF2⊍, ATF4 and PERK expression levels were upregulated in Caco-2 treated with erastin.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, OE alleviates UC by inhibiting oxidative stress. In addition, oxidative stress induces apoptosis through several pathways [ 27 ], and we examined apoptosis in TNBS-induced UC mouse tissues and LPS-treated Caco-2 cells using western blotting, flow cytometry, and TUNEL assays. OE effectively inhibited apoptosis in UC colon tissues and LPS-stimulated Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%